Rancangan Manajemen Kinerja Stratejik PT XYZ - Rakhmadan, Audi; Saragih, Eva Hotnaidah (Research Center and Case Clearing House (RC-CCH) - Sekolah Tinggi Manajemen PPM, 2021)
This study aims to provide recommendations for a performance management system that can be implemented in PT XYZ. The company started implementing performance management in 2017 which is expected to help achieve company goals. However, the current implementation of performance management still needs to be improved, such as performance measurement which only uses behavior and competencies and there is a difference in the performance management process between the corporate and EPD teams. Three theories from Miles & Snow, Schuler & Jackson, and Fombrun are used to get the ideal direction of performance management based on business strategies, while Aguinis theory is used to identify gaps that occur in application in the field. The identification process was applied by document study, analysis of survey results to 40 respondents, and interviews with Senior Performance Management Specialists to obtain a strategic performance management plan that could be used by PT XYZ. Making performance as an indicator of performance appraisal, communication and monitoring of coaching & mentoring results is a recommendation for PT XYZ to improve its performance management.